Anticardiolipin antibodies in ischaemic heart disease: marker or myth?. Issue 5 (May 1993) - Phadke, K V; Phillips, R A; Clarke, D T; Jones, M; Naish, P; Carson, P
Abstract : OBJECTIVES–To assess the incidence and significance of anticardiolipin antibodies after myocardial infarction and in unstable angina. DESIGN–A prospective study of all patients under 60 admitted to the coronary care unit over a 12 month period with a diagnosis of acute myocardial infarction who were followed up for a further 12 months. Patients admitted with unstable angina were similarly assessed but not followed up. Anticardiolipin antibody concentrations were compared with those of age matched controls. SETTING–A district general hospital. PATIENTS–307 patients with acute myocardial infarction and 160 patients with unstable angina. RESULTS–Anticardiolipin antibody concentrations in the two patient groups did not differ significantly from those in the control groups. Antibody concentrations were not related to a history of angina or myocardial infarction nor were they related to subsequent cardiovascular complications. CONCLUSION–This study shows no significant association between anticardiolipin antibody concentrations and either myocardial infarction or unstable angina.